Bone-anchored hearing aid (BAHA): indications, functional results, and comparison with reconstructive surgery of the ear - Bento, Ricardo Ferreira (Int Arch Otorhinolaryngol, 2012)
Introduction: The bone-anchored hearing aid (BAHA) is a bone conduction hearing device that transmits sound directly into the inner ear. It is mainly used in patients with conductive hearing loss associated with aural atresia, but it is also used in those with mixed and sensorineural hearing loss. Goals: To review the main indications for BAHA, to analyze the audiometric results and its benefits for patients and compare them with other treatment modalities, and to compare the literature data with our sample of 13 patients. Method: The research was performed using a database covering works in English, Spanish, and Portuguese, with no limitations in the years when the procedures were performed. We compared the literature data with our results for the 13 patients who underwent BAHA implantation between the years 2000 and 2009. Results: Most of the studies showed that BAHA has great advantages over reconstructive surgery in terms of hearing results, complications, and disease recurrence. The postoperative results for our 13 patients were satisfactory and comparable with the results from the literature, with closure of the air-bone gap in 7 patients and achieving an air-bone gap of 10 dB in 6 patients. No postoperative complications were observed. Conclusion: BAHA is a better treatment option than reconstructive surgery for patients with bilateral deafness. It is a relatively simple surgical procedure with few complications and good hearing results. Recent studies have examined its use in conductive and unilateral sensorineural hearing loss.